Effectiveness of nursing intervention to control fear in patients scheduled for surgery (2018)
Introduction: Fear before surgery has multiple consequences that can be handled by means of nursing interventions.Objective: To determine the effectiveness of two nursing interventions to control fear in patients scheduled for surgery.Materials and methods: Controlled clinical trial carried out in Bucaramanga on 45 people, 15 in the intervention group (preoperative teaching and reduction of anxiety) and 30 in the control group (usual management). Sample size considered power of 0.90, alpha error of 0.05 and intervention ratio of 1:2 in the control group. Block-randomized double-blind clinical trial. Internal consistency of the evaluation format of both result labels of the Nursing Outcomes Classification (NOC) was measured using Chronbach’s alpha. The reproducibility of the formats was determined using Bland-Altman plots. The effects of nursing interventions on fear were established through covariance analysis (ANCOVA).Results: The intervention group presented a coefficient of changes in the “fear control” label, controlled by initial NOC, age and sex of 1.09 (p=0.000). The coefficient of changes in the “knowledge on therapeutic scheme” label was 1.33 (p=0.000).Conclusion: People who received nursing interventions showed a significant decrease in fear compared to those who received usual care (control group).